L’Enlèvement d’Hélène : restauration d’une majolique d’Urbino - Elodie Dehaut (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The article presents a graduation work produced at Institut national du patrimoine. This dissertation is devoted to the study and conservation of a italian majolica plate preserved at the Louvre Museum - Department of Decorative Arts. The restoration has been thought in order to show the object to the public. In the same time, a technical and scientific study examines the use of Golden® Acrylics Fluids Colors associated with three different varnishes by aqueous dispersion.